HERMENEUTIKA DALAM INTERPRETIVE PARADIGM SEBAGAI METODOLOGI PENELITIAN AKUNTANSI - ARY WIRAJAYA, I GDE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 7 No 1 (2012))
Previous researches have discussed mainly about technical and clerical aspects of accounting. This condition has limited the true knowledge of social and organizational role of accounting application. In the context of accounting research in Indonesia, this development is important due to the high variability degree of customs, culture, and religious. It might reflect the true reality and phenomenon in a real depth. Thus it is expected for accounting researchers in Indonesia accept research methodology developed in sociology and anthropology. This article aims to describe in depth the hermeneutic methodology in interpretive paradigm in accounting research.
Keywords: interpretive methodology, hermeneutic, accounting research